2022
DOI: 10.2298/fil2205507l
|View full text |Cite
|
Sign up to set email alerts
|

The wf-rank of topological spaces

Abstract: The class of well-filtered spaces is one of the important class of topological spaces in domain theory. Recently, the existence of well-filterification of T0-spaces has been established. In this paper, we introduce the definition of wf-rank and prove that for any ordinal ?, there exists a T0-space whose wf-rank equals ?.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Two studies evaluating the use of a light trigger during both daytime and nighttime hours to remind PICU (338) or NICU (339) staff when ambient noise levels became excessive demonstrated minor (1-3 dB) reductions in average noise levels but no increase in time spent below recommended noise thresholds. NICU studies aimed to reduce anytime ambient noise via staff education similarly have resulted in minimal or no impact (340,341). A single study in a PICU setting demonstrated significant noise reductions, particularly during evening/nighttime hours, following implementation of a comprehensive delirium bundle, although the bundle components deemed most impactful on noise reduction were not described (303,311).…”
Section: Sleep Hygienementioning
confidence: 99%
“…Two studies evaluating the use of a light trigger during both daytime and nighttime hours to remind PICU (338) or NICU (339) staff when ambient noise levels became excessive demonstrated minor (1-3 dB) reductions in average noise levels but no increase in time spent below recommended noise thresholds. NICU studies aimed to reduce anytime ambient noise via staff education similarly have resulted in minimal or no impact (340,341). A single study in a PICU setting demonstrated significant noise reductions, particularly during evening/nighttime hours, following implementation of a comprehensive delirium bundle, although the bundle components deemed most impactful on noise reduction were not described (303,311).…”
Section: Sleep Hygienementioning
confidence: 99%
“…X is called α d -special (resp., α wf -special), similarly, see [3] and [8], respectively. Remark 4.2 If X is a α k -special space, then α is not a limit ordinal.…”
Section: α K -Special Spacesmentioning
confidence: 97%
“…In [3] and [8], for any ordinal α, there exists a T 0 space whose d-rank (respectively, wf -rank) equals to α. Consider a T 0 space whose k-rank equals to α may be more complex, because we know little about Q k (X).…”
Section: -2mentioning
confidence: 99%
See 1 more Smart Citation